Production Unit-Based Teaching Factory Learning Model (TEFA) to Increase Entrepreneurial Spirit - Pamungkas, Raden Rara Ajeng Rengganis Dhianing; Rusdarti, Rusdarti; Kusumantoro, Kusumantoro (Journal of Economic Education, 2024)
The low quality of vocational school graduates has resulted in the productivity of skilled workers in the industrial world getting worse. Indirectly, the quantity of SMK graduates absorbed is small, due to the distrust of the industrial world to SMK graduates so that the number of unemployed in Indonesia increases. ImplementationTeaching factories in schools are expected to increase students' interest in the future because so far many vocational graduates have become workers compared to being entrepreneurs. The formulation of the problem in this research is how to implement the teaching factory learning model, the results of the implementation and teaching factory learning can increase the entrepreneurial spirit of students at SMKN 1 Semarang. The results of the study show that the application of teaching factory aims to provide work experience and impart skills to students. The process of service and repair services is carried out with a system of division of tasks. The marketing process is not yet optimal because there is no specific strategy to market services and products. The evaluation process has been carried out on an ongoing basis. The output obtained is that students are more confident and have an entrepreneurial spirit. The learning media used in the implementation of the teaching factory are in accordance with operational standards. Equipment and tools owned by SMK N 1 Semarang are adequate and well utilized, and in well-maintained condition.